Heat transfer intensification and scaling mitigation in bubbling-enhanced membrane distillation for brine concentration - Fane, Anthony Gordon (2014)
Membrane distillation (MD) technology is being extensively studied to address operational challenges such as undesired thermal efficiency and scaling phenomenon in recovering valuable solutes and minimizing brine disposal. This study has explored the working mechanisms of utilizing gas–liquid two-phase flow to enhance heat transfer and mitigate scaling formation in MD concentration process, based on the quantification of heat-transfer coefficients and local scaling-resistance associated with bubble size properties.